Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan Demokratis Terhadap Kinerja Personel di Kolinlamil TNI AL Jakarta Utara - Sarah Aprilia; Diyan Lestari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the relationship between work environment and leadership style on the performance of personnel at Kolinlamil. The research sample was 79 cholinlamil. The data test techniques used in this study include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, t test, determination test, multiple linear regression analysis and analysis of mean values. The result of the research shows that the work environment has an effect on performance and democratic leadership style has an effect on performance.